2021
DOI: 10.3390/en14227689
|View full text |Cite
|
Sign up to set email alerts
|

Managing Non-Sewered Human Waste Using Thermochemical Waste Treatment Technologies: A Review

Abstract: The utilisation of micro-scale thermal treatment technologies for non-sewered applications has been emerging as a prominent route for the safe treatment and disposal of high water content hazardous feedstock. This study provides a comprehensive review of the technological concepts practiced up to date in commercial/pilot and small scales for various types of solid fuels. The respective challenges are critically described and discussed to aid in the selection of promising technology for on-site sanitary applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 97 publications
(190 reference statements)
1
6
0
Order By: Relevance
“…These technologies are commonly known to be suitable for low-income countries or situations where sewage infrastructure is inaccessible or difficult to access. This work follows the findings from our earlier study [1], on the selection of pyrolysis as the suitable technology for these applications. A review of the available research on sludge management methods has revealed a major gap in the utilisation of thermal treatment methods for on-site sanitation.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…These technologies are commonly known to be suitable for low-income countries or situations where sewage infrastructure is inaccessible or difficult to access. This work follows the findings from our earlier study [1], on the selection of pyrolysis as the suitable technology for these applications. A review of the available research on sludge management methods has revealed a major gap in the utilisation of thermal treatment methods for on-site sanitation.…”
Section: Introductionsupporting
confidence: 59%
“…The rationale behind the implementation of the chamber is to allow the batch processing of the waste per day to reduce energy consumption in comparison to a constant operation of the reactor. Finally, upon applying thermal loads, FS undergoes pyrolysis degradation with an aim to maximise the reduction of char, the essential rule for hazardous waste treatment [1], and boost the production of syngas with the highest yield and calorific value. Production of highquality syngas enables the chance of convenient energy recovery through its combustion and limits the energy consumption of this system via recycling of the heat which are suggested for future studies.…”
Section: Design and Fast Prototypingmentioning
confidence: 99%
See 2 more Smart Citations
“…The next study [7] provides a comprehensive review of micro-scale thermal treatment technologies for non-sewered practices, which are up to date in commercial/pilot and small scales for various types of solid fuels. Furthermore, the challenges observed with the nominated (pyrolysis) technology are discussed in detail and addressed.…”
mentioning
confidence: 99%